Hot deformation and processing of aluminum alloys - McQueen, H. J. (Boca Raton : CRC Press, 2011)
'PREFACE This book offers readers a fairly comprehensive discussion of the hot working of aluminum and aluminum alloys. It is intended to provide an explanation of the possible microstructural developments that can occur with hot deformation of a variety of alloys and the kind of mechanical properties that can be anticipated. The microstructures that evolve with torsion, compression, extrusion and rolling are presented based on extensive analysis from polarized light optical microscopy (POM), transmission electron microscopy (TEM), x-ray diffraction (XRD) scanning electron-microscopy with electron backscatter imaging (SEM-EBSD) and orientation imaging microscopy (OIM). The microstructural analysis leads to detailed explanations of dynamic recovery (DRV), static recovery (SRV), discontinuous dynamic recrystallization (dDRX), discontinuous static recrystallization (dSRX), grain defining dynamic recovery (gDRV) (formerly geometric dynamic recrystallization gDRX) and continuous dynamic recrystallization involving a single phase (cDRX/1-phase) and multiple phases, (cDRX/2-phase). Hot working is carefully explained in the context of other elevated temperature phenomena, some of which'overlap' hot working. These include creep, superplasticity, cold working and annealing. Creep plasticity occurs at both warm and hot working temperatures, but is usually associated with lower strain-rates and relatively small strains. On the other hand superplasticity involves high tensile strains at similar temperatures, but lower strain rates than utilized in hot working'--
Includes bibliographical references and index.
Keywords: Metals -- Hot working; Aluminum -- Microstructure; Deformations (Mechanics)